2017
DOI: 10.1371/journal.pone.0173007
|View full text |Cite
|
Sign up to set email alerts
|

Density-dependent role of an invasive marsh grass, Phragmites australis, on ecosystem service provision

Abstract: Invasive species can positively, neutrally, or negatively affect the provision of ecosystem services. The direction and magnitude of this effect can be a function of the invaders’ density and the service(s) of interest. We assessed the density-dependent effect of an invasive marsh grass, Phragmites australis, on three ecosystem services (plant diversity and community structure, shoreline stabilization, and carbon storage) in two oligohaline marshes within the North Carolina Coastal Reserve and National Estuari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Numerous studies have shown that the biomass of P. communis is slightly lower than that of S. alterni ora (Medeiros et al, 2013;Theuerkauf et al, 2015;Theuerkauf et al, 2017;Yan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that the biomass of P. communis is slightly lower than that of S. alterni ora (Medeiros et al, 2013;Theuerkauf et al, 2015;Theuerkauf et al, 2017;Yan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This bloom of S. palmeri coincided with a large increase in the ambient biomass of S. horneri in spring 2017, which dramatically reduced the amount of light reaching the bottom in non-removal plots. Studies of aquatic plants and animals, marsh grasses and marine macroalgae have shown that impacts scale with the abundance of an invader (e.g., [51][52][53][54]). In this study, S. horneri had no detectable effects until it reached extremely high abundance, at which point only modest impacts to the native algal community occurred, driven primarily by a single closely related species.…”
Section: Discussionmentioning
confidence: 99%
“…Although the expansion of Phragmites stands into adjacent wetland can be achieved through vegetative lateral expansion (Güsewell & Edwards 1999;Minchinton & Bertness 2003;Brisson et al 2010), recent work has revealed that the advancing front of Phragmites stands can often be composed of multiple genets, highlighting the role of seedling recruitment in Phragmites patch expansion (Kettenring et al 2016). Increased density in mature Phragmites stands correlates to lower native plant biomass and diversity (Holdredge & Bertness 2011; Elsey-Quirk & Leck 2021 but see Theuerkauf et al 2017). Thus, increased shoot density of seedlings recruited near the edge of Phragmites stands may help in outcompeting native plants at the interface between native wetlands and invasive Phragmites.…”
Section: Regional Variation In Seedling Response To Nitrogenmentioning
confidence: 99%